WAQF AND ZAKAT AS PHILANTHROPIC FUNDRAISING INSTRUMENTS IN HIGHER EDUCATION: EVIDENCE FROM MALAYSIAN PUBLIC RESEARCH UNIVERSITIES - Mohd Sadiq, M.M.; Rohayati, M.I.; Abdul Khalil, H.P.S.; Shaharudin, M.S. (Malaysian journal of learning & instruction, 2025)
Purpose – Since 2008, government funding for higher education institutions (HEIs) has declined globally, resulting in reduced quality, higher tuition fees, and increased reliance on philanthropic contributions. This issue has been further exacerbated by the COVID-19 pandemic, prompting many PHEIs to turn to philanthropic fundraising. This study explores how Malaysian public research universities (MRUs) utilise Islamic philanthropic instruments—specifically waqf and zakat—to support student teaching and learning. It examines the successes and challenges of these initiatives and proposes a framework for optimising the use waqf and zakat as sustainable fundraising strategies in Malaysian public higher education institutions (PHEIs). Methodology – A qualitative case study approach was employed. In-depth interviews (both in-person and online) were conducted with nine informants from five selected MRUs, representing four key roles: vice chancellor, bursar/chief financial controller, director of university advancement office/waqf centre, and university legal advisor. Thematic analysis was conducted using both deductive and inductive coding informed by existing literature and emerging themes. Findings – The study revealed two major outcomes: (1) MRUs have successfully mobilised waqf and zakat for fundraising, and (2) these funds have been effectively channelled to enhance teaching, learning and student welfare. Two categories of challenges were also identified: general challenges, such as weak culture of giving and limitations within the tax regime; and specific challenges linked to governance and management of zakat, waqf, and university foundations (yayasan). The study proposes several initiatives to improve financial sustainability, including public awareness campaigns, tax policy reforms, strategic collaborations with State Islamic Religious Councils (SIRCs), and formalised agreements on fund allocation. Significance – This study contributes to the growing body of knowledge on Islamic philanthropic fundraising in higher education. The insights provided offer practical implications for Malaysian PHEIs seeking to enhance financial sustainability through waqf and zakat. In doing so, it supports the broader objective of achieving Sustainable Development Goal 4 (SDG 4) on inclusive and equitable quality education.